Modulation of Vascular Human Endothelial and Rat Smooth Muscle Cell Growth by a Fucosylated Chondroitin Sulfate from Echinoderm - Tapon-Bretaudière, J.; Drouet, B.; Matou, S.; Mourão, P. A. S.; Bros, A.; Letourneur, D.; Fischer, A. M. (Thrombosis and Haemostasis, 2000)
Fucosylated chondroitin sulfate is a glycosaminoglycan extracted from the sea cucumber Ludwigothurea grisea. This polysaccharide has the same structure as a mammalian chondroitin sulfate but some of the glucuronic acid residues display sulfated fucose branches. Anticoagulant and antithrombotic properties of fucosylated chondroitin sulfate have already been described. In order to further investigate its potential therapeutic use as an antithrombotic agent, we studied its effect on vascular smooth muscle cell (SMC) proliferation and endothelial cell proliferation, migration and Tissue Factor Pathway Inhibitor (TFPI) release. The experiments were performed on SMC from rat thoracic aorta and on human umbilical vein endothelial cell (HUVEC) in culture with or without added fibroblast growth factors (FGF-1 and FGF-2). Our results showed that: (i) fucosylated chondroitin sulfate had a strong inhibitory effect on SMC proliferation (IC50 =10 ± 5 µg/ml) and (ii) no effect on HUVEC proliferation and migration assays, in the absence of exogenous FGF, while heparin had inhibitory effects; (iii) fucosylated chondroitin sulfate (10 µg/ml) enhanced FGF-1 and FGF-2 induced HUVEC proliferation by 45% (145.4 ± 7.2%) and 27% (126.9 ± 4.2%), respectively; (iv) on FGF-induced HUVEC migration, fucosylated chondroitin sulfate (10 µg/ml) had a strong enhancing effect with FGF-1, +122% (222.2 ± 15.8%), three times higher than that of heparin, and a lower enhancing effect with FGF-2, +43% (142.7 ± 4.6%), whereas heparin had no effect; (v) fucosylated chondroitin sulfate stimulated TFPI release, mainly on the free form, +98% (198.2 ± 25.%). In addition, the structural features of the polysaccharide associated with its biological activity were resolved using chemically modified fucosylated chondroitin sulfates. Sulfated fucose branches groups are essential to the potentiating effect of the polysaccharide on HUVEC proliferation and migration. Surprisingly, removal of fucose branches from the fucosylated chondroitin sulfate did not abolish TFPI release. Finally, partial reduction of the glucuronic acid carboxyl groups limited the potentiating effect on HUVEC proliferation and migration but did not affect TFPI release. In conclusion, this fucosylated chondroitin sulfate from invertebrate origin reveals useful properties for an antithrombotic agent: inhibition of SMC proliferation, enhancement of endothelium wound repair and TFPI release. These properties on vascular cells, associated with a low bleeding tendency and an antithrombotic activity, strongly suggest its potential use as a new therapeutic agent in arterial thrombosis and restenosis, with a more favorable effect than heparin.
Keywords: Sulfated polysaccharides; endothelial cells; smooth muscle cells; vascular cell growth; growth factors